2022
DOI: 10.3390/nu14030587
|View full text |Cite
|
Sign up to set email alerts
|

Plate Waste Forecasting Using the Monte Carlo Method for Effective Decision Making in Latvian Schools

Abstract: Food waste is a global problem, which becomes apparent at various stages of the food supply chain. The present research study focuses on the optimization of food consumption in schools and effective food management through data-driven decision making within the trends: zero food waste and digital transformation. The paper presents a plate waste forecasting system based on mathematical modeling and simulation using the Monte Carlo method, which showed an RMSE equal to ±3% and a MAPE of 10.15%. The solution base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…non-standard food (Prescott et al, 2019), the presence of alternative foods (Falasconi et al, 2015) or special diets in schools (Eriksson et al, 2017). Food leftovers could be reduced by providing enough time to eat (Kodors et al, 2022;Painter, Thondhlana, & Kua, 2016), as the amount of food waste is affected by the duration of lunch, a sense of urgency and a lack of time to eat (Burton et al, 2022;Painter, Thondhlana, & Kua, 2016;Qian et al, 2021;Silvennoinen, Nisonen, & Pietiläinen, 2019). Several research studies emphasized the role of a lunch supervisor as crucial, as a lack of control over food leftovers made by schoolchildren is a major source of food waste (Derqui & Fernandez, 2017;Martins et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…non-standard food (Prescott et al, 2019), the presence of alternative foods (Falasconi et al, 2015) or special diets in schools (Eriksson et al, 2017). Food leftovers could be reduced by providing enough time to eat (Kodors et al, 2022;Painter, Thondhlana, & Kua, 2016), as the amount of food waste is affected by the duration of lunch, a sense of urgency and a lack of time to eat (Burton et al, 2022;Painter, Thondhlana, & Kua, 2016;Qian et al, 2021;Silvennoinen, Nisonen, & Pietiläinen, 2019). Several research studies emphasized the role of a lunch supervisor as crucial, as a lack of control over food leftovers made by schoolchildren is a major source of food waste (Derqui & Fernandez, 2017;Martins et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…non-standard food (Prescott et al, 2019), the presence of alternative foods (Falasconi et al, 2015) or special diets in schools (Eriksson et al, 2017). Food leftovers could be reduced by providing enough time to eat (Kodors et al, 2022;Painter, Thondhlana, & Kua, 2016), as the amount of food waste is affected by the duration of lunch, a sense of urgency and a lack of time to eat (Burton et al, 2022;Painter, Thondhlana, & Kua, 2016;Qian et al, 2021;Silvennoinen, Nisonen, & Pietiläinen, 2019). Several research studies emphasized the role of a lunch supervisor as crucial, as a lack of control over food leftovers made by schoolchildren is a major source of food waste (Derqui & Fernandez, 2017;Martins et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Derqui et al [ 11 ] investigated food waste in four schools and noted different educational characteristics and models of catering businesses that may differ between cooking in school kitchens and those involving delivery. Kodors et al [ 30 ] attempted to make proposals for decision-making in education and school lunch provision services using simulation methods to consider menu composition and lunchtime with which children could be satisfied. Our study provides evidence that the school lunch delivery system affects leftover food.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that this study was conducted mostly in junior high schools may have influenced the differences in the target facilities. In addition to environmental factors within classrooms, several studies have shown that large portion sizes and short eating times decrease students’ intentions and increase food waste [ 9 , 19 , 21 , 30 ]. From the perspective of the number of students per class, a homeroom teacher can provide detailed instruction when there are fewer students per class.…”
Section: Discussionmentioning
confidence: 99%